Evaluation Of Interest Rate Free In Indonesian Islamic Banking - Roikhan Mochamad Aziz; Syahrul Syahrul (IJECA (International Journal of Education and Curriculum Application), 2018)
The purpose of this study reviewed the analysis and discussion in a thesis entitled "Analysis of Effect of Non Performing Financing (NPF), assets of Islamic Banking and Bank Indonesia Certificates Sharia (SBIS) Financing Against Islamic Banking in Indonesia in 2010-2013". This research methodusing descriptive qualitative method in which these two methods are analyzed and explained by the subjective nature or in accordance with the object. The data used is qualitative data that comes from two sources, namely primary data and secondary data. Then the data is formulated and interpreted so neatly into one. The data collection is done by observation, interview, documentation, and literature. The results of this research are variable Non Performing Financing (NPF), assets of Islamic Banking and Bank Indonesia Certificates Sharia (SBIS) mempunai significant effect on the financing of Islamic banking in Indonesia.